Young men’s barriers to and facilitators of utilising HIV-testing services in South Africa - Ndlovu, Sithembiso M.S.; Ross, Andrew; Ndirangu, James (Southern African journal of HIV medicine, 2025)
BackgroundIn South Africa, men are less likely than women to use HIV-testing services (HTS). They are also unlikely to start and adhere to antiretroviral therapy until the virus has progressed to advanced AIDS stages.ObjectivesTo explore young men’s barriers to and facilitators of accessing and utilising HTS at the rural Driefontein and peri-urban Steadville Township in Ladysmith, KwaZulu-Natal (KZN) province, and to develop a comprehensive framework of care for young men to encourage and support them to utilise HTS at primary healthcare facilities.MethodThis exploratory-descriptive qualitative study entailed using semi-structured interviews conducted via WhatsApp and landline audio calls with 17 young men between 18 years and 30 years of age in Steadville and Driefontein communities in KZN in September 2021. Participants were purposively and conveniently sampled, and the data were analysed thematically.ResultsAll participants were unmarried isiZulu African men experienced with HTS in the last 4 years. Fear of an HIV-positive test result, limited HTS knowledge, and stigma around HIV and AIDS were challenges linked to HTS utilisation. Unsafe sexual encounters, voluntary medical male circumcision, early virus-detection, having a significant other living with HIV, and HIV-status curiosity encouraged young men to utilise HTS.ConclusionVarious barriers and facilitators to HTS utilisation, are key for consideration when deriving contextual interventions acceptable to young men as efforts to raise awareness and attract and retain men in care.